2012
DOI: 10.1093/humrep/des322
|View full text |Cite
|
Sign up to set email alerts
|

Are digestive symptoms in women presenting with pelvic endometriosis specific to lesion localizations? A preliminary prospective study

Abstract: The North-West Inter Regional Female Cohort for Patients with Endometriosis (CIRENDO) is financed by the G4 Group (The University Hospitals of Rouen, Lille, Amiens and Caen). No financial support was specifically received for this study. The authors declare no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 11 publications
4
50
0
1
Order By: Relevance
“…endometriosis infiltrating the intestinal muscular layer (1), appears to affect about one tenth of women with the endometriotic disease (2,3). Symptoms may be associated not only with the degree of endometriotic infiltration and bowel lumen restriction but also with lesion localization (1,4). However, most patients with deep bowel endometriosis complain of cyclic and non-cyclic symptoms, such as abdominal bloating, intestinal cramping, diarrhea and constipation, without obvious obstruction to stool passage (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…endometriosis infiltrating the intestinal muscular layer (1), appears to affect about one tenth of women with the endometriotic disease (2,3). Symptoms may be associated not only with the degree of endometriotic infiltration and bowel lumen restriction but also with lesion localization (1,4). However, most patients with deep bowel endometriosis complain of cyclic and non-cyclic symptoms, such as abdominal bloating, intestinal cramping, diarrhea and constipation, without obvious obstruction to stool passage (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…However, most patients with deep bowel endometriosis complain of cyclic and non-cyclic symptoms, such as abdominal bloating, intestinal cramping, diarrhea and constipation, without obvious obstruction to stool passage (Figures 1 and 2). Symptoms may be associated not only with the degree of endometriotic infiltration and bowel lumen restriction but also with lesion localization (1,4). The rectosigmoid colon is the most frequently involved intestinal tract, followed by isolated nodules of the proximal sigmoid and by lesions of the terminal ileus and cecum (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the quality of adenomyosis patient's life was significantly improved after LNG-IUS insertion. the SF-36-based survey has been used among 931 women with endometriosis treated in 12 tertiary care centers in 10 countries that investigated the effect of endometriosis on education, work and social wellbeing, endometriosis -associated symptoms and health-related quality of life [23], and also used to types and frequency of digestive symptoms in patients with different localizations of pelvic endometriosis and which specific symptoms are related to rectal stenosis [24]. To the best of our knowledge, this Note: Continuous variables are expressed as mean ± standard deviation; Paired-samples t test as appropriate; a P < 0.001 vs before treatment, b P < 0.001 vs after 1 month, c P < 0.001 vs after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Deep infiltrating endometriosis of the rectum (DIER) is responsible for various digestive symptoms such as dyschesia, tenesmus, predominant catamenial diarrhoea or constipation, rectal bleeding, and bloating [1]. In severe cases, progressive stenosis of the lumen can lead to colorectal subocclusion or occlusion [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Medical treatment is then used to prevent recurrences in women with no wish for future pregnancy. When digestive complaints are closely related to menstrual periods [1], gastrointestinal symptoms are also relieved in most patients [14][15][16]. In order to support this approach, more detailed data are required on the efficacy of medical treatment in improving symptoms and gastrointestinal quality of life in patients with colorectal endometriosis.…”
Section: Introductionmentioning
confidence: 99%